Numerical and experimental study of the transverse creep-recovery behavior of bamboo culm (Dendrocalamus hamiltonii) - Ounjaijom T. (2017)
© 2016, Walailak University. All rights reserved. Hot compression creep-recovery behavior in the transverse direction of bamboo culm was studied. Creep-recovery tests were performed to investigate nonlinear viscoelastic strain. Long-term uniaxial creep-recovery laboratory tests were carried out at 5 different constant applied stress levels inside a boiling water bath. The Burgers model was used to characterize the observed creep data and the Weibull distribution equation was used to characterize the observed recovery data. The models successfully describe the main features for the investigated material and shows good agreement with the experimental creep-recovery data.